The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1016/0014-5793(89)81094-4
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of antibodies to synthetic peptides of proNGF with in vitro synthesized NGF precursors

Abstract: Sera raised against three synthetic peptides that reproduce sequences of the pro-nerve powth factor (proNGF) protein were tested in immunoprecipitation experiments using in vitro translation products of SP6-directed NGF mRNA in a rabbit reticulocyte lysate. The interaction of these antibodies with bacterially synthesixed chimeric preproNGF was also examined. Digestion of the translation products by the y-subunit generated the 22 and 18 kDa intermediates. A predominant 13 kDa intermediate was obtained after dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…While both the NGF␥ subunit and trypsin appeared to cause a small increase in the electrophoretic mobility of the NGF precursor, these proteases failed to cleave the precursor to a mature form, while resulting in an apparent decrease in precursor. This suggests a different folding of precursor, since it has been observed that NGF␥ and trypsin degrade the mature NGF␤-moiety of in vitro NGF precursor translation products, suggested to be a consequence of improper folding [6][7][8]23]. While neither NGF␥ nor trypsin appeared to cleave the stromal NGF precursor to NGF␤, it is possible that another enzyme could cleave the protein to the mature form.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…While both the NGF␥ subunit and trypsin appeared to cause a small increase in the electrophoretic mobility of the NGF precursor, these proteases failed to cleave the precursor to a mature form, while resulting in an apparent decrease in precursor. This suggests a different folding of precursor, since it has been observed that NGF␥ and trypsin degrade the mature NGF␤-moiety of in vitro NGF precursor translation products, suggested to be a consequence of improper folding [6][7][8]23]. While neither NGF␥ nor trypsin appeared to cleave the stromal NGF precursor to NGF␤, it is possible that another enzyme could cleave the protein to the mature form.…”
Section: Discussionmentioning
confidence: 95%
“…A similar effect of epitope masking and/or inability to recognize altered conformational epitopes may account for the inability of anti-NGF␤ to recognize intermediate forms of pro-NGF. In addition, differences in relative abundance of NGF precursors between sample preparations have been described [7] that could also account for differences in propeptide antibody recognition of precursor proteins. On infrequent occasions, NGF immunoblots of hPS preparations have also identified a protein with approximate M r of 18 kDa (data not shown), consistent with differences in the relative abundance of NGF precursors described previously [7].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations